2008
DOI: 10.1111/j.1365-4632.2008.03308.x
|View full text |Cite
|
Sign up to set email alerts
|

Type B pigmentary demarcation lines in a Chinese amenorrheic woman

Abstract: A 51‐year‐old Chinese woman (phototype III) presented to our dermatology clinic with a 3‐month history of asymptomatic pigmented maculae on the lower limbs that developed in the 11th month of amenorrhea. She had noticed no other areas of pigmentary change and denied any inflammatory episode or topical medication before their development. No personal or family history of hormonal imbalance or pigmentary demarcation lines (PDLs) was found. Physical examination revealed broad, band‐like pigmentation symmetrically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…However, a single case report of amenorrheic Chinese woman documents low estradiol and FSH with type B PDL. [4] It is difficult to correlate the abnormal hormonal profile with pathogenesis of facial PDL in this study as one does not know if abnormal hormonal levels preceded the onset of PDL. The heterogeneous nature of hormonal levels further complicates the interpretation.…”
mentioning
confidence: 98%
“…However, a single case report of amenorrheic Chinese woman documents low estradiol and FSH with type B PDL. [4] It is difficult to correlate the abnormal hormonal profile with pathogenesis of facial PDL in this study as one does not know if abnormal hormonal levels preceded the onset of PDL. The heterogeneous nature of hormonal levels further complicates the interpretation.…”
mentioning
confidence: 98%
“…Ma et al. reported a Chinese amenorrheic woman with type B lines 11 . Our patient is a Chinese girl of normal intelligence and development and without remarkable medical history.…”
Section: Types and Subtypes Of Pigmentary Demarcation Linesmentioning
confidence: 65%
“…9,10 Ma et al reported a Chinese amenorrheic woman with type B lines. 11 Our patient is a Chinese girl of normal intelligence and development and without remarkable medical history. Lesions such as those on our subject may sometimes be misdiagnosed as vitiligo, depigmented nevi, or ash-leaf maculae of tuberous sclerosis.…”
mentioning
confidence: 96%
“…The role of hormonal alterations in PDLs is further supported by the report of a nonpregnant woman with type B PDLs, receiving long-term estrogenic medication6. An amenorrheic woman with type B PDLs and decreased titers of estradiol and elevated levels of follicle-stimulating hormone has also been reported7. In the latter case, the hormonal changes were different from the changes in sex hormones during pregnancy.…”
Section: Discussionmentioning
confidence: 93%